A DNA‐Based Label‐Free Artificial Tongue for Pattern Recognition of Metal Ions. Issue 39 (21st June 2017) - Qiu, Hao; Pu, Fang; Ran, Xiang; Ren, Jinsong; Qu, Xiaogang
Abstract: An array‐based sensing method offers several advantages for detecting various analytes. DNA molecules as sensor elements have attracted considerable interest owing to their unique properties. Here, a label‐free sensor array using DNA and commercially available dyes to differentiate metal ions is reported. Based on the different interactions between dye‐bound DNA and metal ions, the fluorescence intensities of the sensor elements are changed to different degrees. In this way, fourteen metal ions can be efficiently distinguished by principal component analysis (PCA) and hierarchical cluster analysis (HCA). A highly sensitive discrimination of metal ions with 92.8 % identification accuracy can be achieved. The present work provides a simple and convenient method for the construction of a DNA‐based sensor array. Abstract : DNA molecules as sensor elements attract considerable interest owing to their unique properties. Here, a label‐free sensor array using DNA and commercially available dyes to differentiate metal ions is reported. In this way, fourteen metal ions can be efficiently distinguished by principal component analysis (PCA) and hierarchical cluster analysis (HCA). The work provides a simple and convenient method for the construction of DNA‐based sensor arrays.